Antifungal Effectiveness Test of Gleichenia linearis Burm. (Farm) Leaf Extract on Candida albicans Fungi - Azis, Asyari Al Hutama; Pratiwi, Yani; Nurfirawati, Nurfirawati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The fern leaf (Gleichenia linearis Burm.) is a species of fern known to have potential as an agent that inhibits fungal growth. This study aims to test the antifungal effectiveness of fern leaf extract against the growth of Candida albicans and determine the most effective concentration. The extract was obtained through 70% ethanol maceration from 500 g of dried leaves, then formulated in concentrations of 5%, 10%, and 20%. Disc diffusion tests were carried out on SDA media, with 10 μg ketoconazole as a positive control and 70% ethanol as a negative control. The results showed an average inhibition zone of 4.66 mm (5%), 6.91 mm (10%), and 10.83 mm (20%), while the positive control was 18.54 mm and the negative control showed no inhibition. The Kruskal-Wallis test (Sig.) <0.05 was used as a reference resulting in a p value = 0.009, indicating a significant difference between groups. The results of phytochemical screening showed the presence of alkaloids, flavonoids, saponins, tannins, phenolics, and terpenoids. In conclusion, fern leaf extract is effective in inhibiting the growth of Candida albicans, with a concentration of 20% being the most effective.